Psychometric properties of the Chinese version physical literacy assessment questionnaire among high school students in Gansu, China - Qu, Zilu; Wu, Jiarun; Kueh, Yee Cheng; Ye, Dongqing; Kuan, Garry (PeerJ, 2025)
Introduction The concept of physical literacy (PL) originated from the philosophy of lifelong sports, and its development is crucial for achieving lifelong sports goals. The Portuguese Physical Literacy Assessment Questionnaire (PPLA-Q) is a tool designed to assess the physical literacy of high school students, demonstrating good reliability and validity. The aim of this study is to translate and adapt the PPLA-Q into Chinese (PPLA-Q-C) and validate its applicability among adolescents in Gansu, China through confirmatory factor analysis (CFA). Methods A total of 780 middle school students from Gansu Province, China, aged 15–18, participated. After screening, the final sample size was 729. The English PPLA-Q was translated into Chinese and validated through expert review and pre-testing. Data were collected in September 2022 via a self-reported survey, with an effective response rate of 93.5%. Data analysis was conducted using Mplus 8.3 with the robust maximum likelihood (MLR) estimator. Confirmatory factor analysis (CFA) assessed model fit using standardized root mean square residual (SRMR), root mean square error of approximation (RMSEA), Tucker-Lewis index (TLI), and comparative fit index (CFI) indices. Construct validity was evaluated through composite reliability (CR), average variance extracted (AVE), and factor correlations. The study followed ethical guidelines and received approval from Universiti Sains Malaysia’s ethics committee. Results All observed items exhibited high factor loadings, confirming that the assumed model, consisting of 40 items grouped into four latent variables, was consistent with the original model. The CFA model demonstrated a good fit with the data, as indicated by fit indices: RMSEA = .024 (90% CI [.020–.027]), CFI = .978, TLI = .977, SRMR = .032. Conclusion The final measurement model comprised 40 items, all retained and considered acceptable for the sample. The study results suggest that the Chinese version of PPLA-Q (PPLA-Q-C) is effective and reliable for assessing the PL of high school students in Gansu Province, China. Education practitioners and policymakers can utilize the PPLA-Q-C framework in their future work to assess the PL of Chinese-speaking students.
Keywords: PPLA-Q; Physical activity; CFA; Sample size